2016
DOI: 10.1186/s12913-016-1839-y
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of general practitioners and selected specialist physicians by car and by public transport in a rural region of Germany

Abstract: BackgroundThe accessibility of medical care facilities in sparsely populated rural regions is relevant especially for elderly people which often represent a large segment of the population in such regions. Elderly people have higher morbidity risks and a higher demand for medical care. Although travelling with private cars is the dominating traffic mode in rural regions, accessibility by public transport is increasingly important especially because of limited mobility of elderly people. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 19 publications
1
38
0
11
Order By: Relevance
“…Our findings concur with former national studies showing that people living in rural areas mainly use their (own) car in order to ensure their mobility [4, 43]. Our study adds accordance for medical consultations.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings concur with former national studies showing that people living in rural areas mainly use their (own) car in order to ensure their mobility [4, 43]. Our study adds accordance for medical consultations.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to transportation factors and healthcare access, an American study focusing on rural areas reported that annually, public transportation users made four more visits for chronic medical care than nonusers . However, some studies reported access to medical and dental care is reduced if medical facilities are geographically far from people's houses, especially those with low income and/or those who are disadvantaged . From previous and present studies, public transportation is considered to reduce geographical barriers in access to care.…”
Section: Discussionmentioning
confidence: 81%
“…For example, Stentzel et al. showed that, while the majority of the population in a rural region such as Western Pomerania‐Greifswald spend an acceptable amount of time in the car (80 % with a travel time below 20 minutes) to get to the nearest specialist (in this case: ophthalmologist, internist, and urologist), the average time spent on public transportation to see these specialists is more than two hours (round trip). The study by Augustin et al.…”
Section: Discussionmentioning
confidence: 99%